CONGENITAL HEART DISEASES IN INFANTS PRESENTING WITH RESPIRATORY DISTRESS TO A TERTIARY CARE HOSPITAL - Hussain, Mohammad; Hayat, Mohsin; Irshad, Muhammad (Journal of Postgraduate Medical Institute, 2021)
Objective: To determine the frequency of congenital heart diseases (CHD) in infants admitted with respiratory distress to pediatrics unit. Methodology: This cross-sectional study was conducted on 261 infants, presenting with respiratory distress and treated as indoor patients in the pediatrics department, Lady Reading Hospital, Peshawar. Non probability purposibe sampling technique was used to enroll the sample. History was taken and infants were examined by a consultant pediatrician. The findings were recorded on a pre-designed proforma. Trans-thoracic echocardiography was performed at the cardiology unit of the same hosptial. SPSS v. 20.0 was used as a statistical tool. Results: Out of 261 infants, 5 (1.9%) were found to have congenital heart disease with a mean age of 6.0±4.6 months. Female predominance was noted (n=143, 54.8%). Maternal age was 30.0±10.5 years. Pulmonary stenosis was the most CHD, reported in 2 (0.7%) patients, followed by ventricular septal defect, atrial septal defect and tetralogy of fallot, reported in 1 (0.4%) patient each. Conclusion: The study reported a low incidence of CHD among infants with respiratory distress and may come to attention as standalone respiratory distress in infants.